A clinicopathological study on overexpression of cyclin D1 and of p53 in a series of 248 patients with operable breast cancer. - Michalides, R. (Nature Publishing Group, 1996)
Overexpression of cyclin D1 is frequently found in various types of human tumours and results from clonal rearrangement and/or amplification involving chromosomal region 11q13. In order to evaluate the pathological relevance of cyclin D1 overexpression in human breast cancer, we generated a polyclonal antiserum against the carboxy-terminal part of the cyclin D1 protein. After affinity purification, the antiserum specifically detected overexpression of cyclin D1 in formalin-fixed, paraffin-embedded tumour material also. The intensity of the nuclear stainings was, in general, proportional to the degree of cyclin D1 amplification. We did not encounter significant variability of staining within individual tumours with overexpression of cyclin D1. Overexpression of cyclin D1 appeared to be associated with oestrogen receptor-positive breast tumours, but not with any other clinicopathological parameter tested. Overexpression of cyclin D1 was not prognostic value for recurrence of survival in a consecutive series of 248 operable breast cancer patients (stage I and II). Overexpression of p53 was also not of prognostic significance in this series, but was associated with undifferentiated histology and oestrogen receptor-negative breast tumours, as has been reported previously by others. A high proportion of breast tumours with a low grade of malignancy in this series of operable breast cancer patients may explain discrepancies concerning the prognostic value of amplification and of overexpression of cyclin D1. IMAGES: